Differences in Video Gaming Habits among Young Adults in Spain Disaggregated by Sex - Espada Mairata, Irene; McGowan, Nadia; González-Fraile, Eduardo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study examines gender differences in video game usage among young adults in Spain. A cross-sectional observational study was conducted with 500 participants aged 18 to 24. The findings show that women prefer playing solo (69.8%), while men favor online multiplayer games (55.7%). Men spend more time gaming and prefer action and sports genres, whereas women gravitate toward social and simulation games. Additionally, women report lower self-perceived gaming skills in certain tasks. The study concludes that significant gender differences exist in gaming habits, genre preferences, and skill perception.